Preferences of patients with depression for medication management: a discrete choice experiment - Xie, Peng; Guo, SiZhu; Yang, Hao; Wang, YanFen; Ming, WenWen; Li, HuangYan; Li, Hui-qin (Frontiers in Psychiatry, 2025)
BackgroundDepression threatens people’s health and imposes heavy economic burden on society. Oral antidepressants are the first-line treatment for depression. However, poor adherence in depressed patients contributes to poor clinical outcomes. Effective medication management can improve patient adherence, but the current approaches to medication management in depression have shown limited success. Understanding patients’ needs and preferences can help improve their medication adherence. There are no data on the preferences of depressed patients in developing countries.ObjectiveA discrete choice experiment (DCE) was conducted to elicit and quantify the preferences of people with depression for medication management, and to provide references for the development of effective medication management strategies to improve the medication adherence of people with depression.MethodsThe design principles of discrete choice experiments were used to develop the survey instrument. Attributes included adverse reactions, provider, follow-up frequency, cost, follow-up method, and convenience of purchase. A mixed logit model was used to estimate the preferences, willingness to pay (WTP), subgroup analyses based on relapse, and the uptake rates of different medication management program using the NLCOM command.ResultsThe preferences of 373 people with depression were analyzed. The six attributes included in this study had a significant impact on preferences of people with depression (P < 0.05). Slight adverse reactions were the most important attribute level (coefficient =0.905), with the highest willingness to pay, and increased program uptake by 0.362. Patients who did not experience recurrence preferred to go to the pharmacy to purchase antidepressants on site. In terms of follow-up methods, those with recurrence experience preferred remote follow-up. Providing face-to-face and telephone/we-chat follow-up by psychiatrists, and with slight adverse reactions, the probability of receiving medication management program increased by 0.478, which was close to the optimal medication management program.ConclusionThe formulation of medication management strategies should be rooted in the preferences of people with depression. The impact of recurrent depression experiences on preferences should be considered when forming collaborative care teams consisting of psychiatrists, psychiatric nurses, and family physicians to address the complex and multifaceted needs of people with depression.